Árangur fleyg- og geiraskurða við lungnakrabbameini á Íslandi - Ásgeir Alexandersson; Steinn Jónsson; Helgi J. Ísaksson; Tómas Guðbjartsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2011)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) Introduction: A sublobar resection is performed on patients with non-small cell lung cancer (NSCLC) who are not candidates for a lobectomy due to reduced pulmonary function or comorbid disease. The aim of this study was to investigate the outcomes of these operations in Iceland. Material and methods: A retrospective study of all patients with NSCLC who underwent wedge resection or segmentectomy with curative intent during 1994-2008. Data on indication, pathological TNM-stage, complications and overall survival was analyzed. All histological samples were re-evaluated. Results: Forty four patients underwent 42 wedge and 5 segmental resections (age 69.1 yrs, 55.3% female), with 38.3% of cases detected incidentally. The majority of patients (55.3%) had a history of coronary artery disease and 40.4% had chronic obstructive pulmonary disease. Mean operative time was 83 minutes (range 30-131), mean intraoperative bleeding was 260 ml (range 100-650) and median hospital stay was 9 days (range 4-24). Pneumonia (14.9%) and prolonged air leakage (12.8%) were the most common complications. Two patients had major complications and 36.2% stayed in the intensive care unit overnight. No deaths occurred within 30 days of surgery. Adenocarcinoma was the most common histological type (66.7%). Most cases were stage IA/IB (78.7%), 17.0% were stage IIA/IIB and 4.3% were stage IIIA. One and 5 year survival was 85.1% and 40.9% respectively. Conclusion: In Iceland, both survival and complication rate after sublobar resection for NSCLC are comparable to results published for lobectomies, even though a higher percentage of patients have underlying cardiopulmonary disease. Inngangur: Hefðbundin aðgerð við lungnakrabbameini öðru en smáfrumukrabbameini er blaðnám. Í völdum tilvikum, einkum þegar lungnastarfsemi er mikið skert, er gripið til fleyg- eða geiraskurðar. Markmið þessarar rannsóknar var að kanna árangur þessara aðgerða ...